TAFSIR AYAT-AYAT NEUROSAINS DAN AYAT-AYAT BERAKHIRAN AFALAA TA’QILUUN - Heru Widi Widodo (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
The advantage of humans and other creatures is that they are able to function the mind. As with other beings, God is also gifted with reason. Reason can also be called neuroscience. Humans are